2004
DOI: 10.1063/1.1831252
|View full text |Cite
|
Sign up to set email alerts
|

Digital system for vacuum and gas-filled devices testing

Abstract: Electrical system for measurement of breakdown voltage of vacuum and gas-filled tubes using a dynamic method Rev.A method for measuring the presampled MTF of digital radiographic systems using an edge test device Med.This article describes an improved electrical system aimed at measuring and data acquisition of the breakdown voltage of vacuum and gas-filled devices at low pressures using a discretized dynamic method. The previous system [M. M. Pejovic, C. S. Milosavljevic, and M. M. Pejovic, Rev. Sci. Instrum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It should be expected that U b could have a fix value U s , only for very small values of k, theoretically for k ¼ 0. Our previous research for neon-filled tube 19) have shown that U s as a deterministic quantity can be estimated from U b ¼ f ðkÞ dependence, where U b is the mean value of breakdown voltage U b . The estimation is performed in a following way.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be expected that U b could have a fix value U s , only for very small values of k, theoretically for k ¼ 0. Our previous research for neon-filled tube 19) have shown that U s as a deterministic quantity can be estimated from U b ¼ f ðkÞ dependence, where U b is the mean value of breakdown voltage U b . The estimation is performed in a following way.…”
Section: Resultsmentioning
confidence: 99%
“…This voltage is increased in steps U p during time intervals t p by Keithley model 2400 until breakdown (see ref. 19 for more details).…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to perform several measurements of U b , and to use mean values U b (in our experiments U b represents the mean value of 100 measured breakdown voltages U b for each value of k). The breakdown voltage U b was measured by an electronic system described in [27]. The U s value was estimated by fitting the U b = f (k) dependence and finding the intersection of the fitting line with the U b axis (for k = 0).…”
Section: Resultsmentioning
confidence: 99%
“…increasing voltage in steps until breakdown [17]. The experimental setup for measurements of dynamic breakdown voltage is given in paper [18]. The value of static breakdown voltage U s was estimated by fitting the U b = f (k) dependence (k = U p /t p is the voltage increase rate; U p is the voltage step and t p is the time interval between the two successive voltage steps) and finding the intersection of the fitted line with the U b -axis.…”
Section: Methodsmentioning
confidence: 99%